Improved cyclic stability of layered lithium cobalt oxide at high potential via cathode electrolyte interphase formed by 4-(trifluoromethyl) benzonitrile. (1st December 2015) - Wang, Xianshu; Liao, Xiaolin; Huang, Wenna; Xing, Lidan; Liao, Youhao; Huang, Qiming; Xu, Mengqing; Li, Weishan
Highlights: 4-TB is an effective electrolyte additive for improving the cyclic stability of LiCoO2 under 4.5 V. 4-TB combines with Co(IV) and is oxidized preferentially forming CEI film on LiCoO2 . CEI protects LiCoO2 from structural destruction and suppresses electrolyte decomposition. Abstract: The cyclic stability of LiCoO2 as cathode of lithium ion battery under 4.5 V is improved by using 4-(trifluoromethyl) benzonitrile (4-TB) as an electrolyte additive. In a standard (STD) electrolyte (1.0 mol/L LiPF6 in EC/EMC/DMC, 1/1/1 by volume) containing 0.5 wt.% 4-TB, LiCoO2 exhibits an improved cyclic stability when the end-off charge potential is increased to 4.5 V. The characterizations, from XRD, ICP, SEM, FTIR, and XPS, demonstrate that a cathode electrolyte interphase (CEI) film is formed on LiCoO2 from 4-TB, which suppresses the successive decomposition of STD electrolyte and prevents LiCoO2 from crystal destruction. Theoretical calculations confirm that 4-TB is adsorbed and oxidized on LiCoO2 preferentially to the carbonates in electrolyte, forming the protective CEI film.